Girls Wellbeing: Anxiety And Mathematical Achievement At The End Of Primary School - Salinas, Gianela (2022)
The aim was to determine whether there is a relationship between anxiety and mathematical performance in sixth grade primary school students, and if gender differences exist. Mathematics anxiety is a type of anxiety that affects this specific academic area or it is triggered by it. Studies have shown that students from the beginning of adolescence show mathematics anxiety and it increases as they progress through an academic environment. There is evidence to suggest that two important factors play a role in mathematics anxiety: the educational level and gender. There is consistent evidence that girls tend to be more affected by it than boys, but this has not been studied in primary school. 149 sixth grade students (mean age 140.5 months) from four schools in two Peruvian cities participated in two assessments, one that aimed to assess their level of mathematical anxiety and one that aimed to assessed their mathematical achievement. Results revealed that although there is no relation between mathematical anxiety and mathematical performance in sixth grade students, there are gender differences. Females (n=72) have an almost significant relationship (r=-.227, p=0.56). Presenting a lower mean in mathematics achievement compared to their male counterpart (x=14.05 and 15.71 respectively) and higher anxiety (x=49.92 and 42.64 respectively). This evidence has theoretical and practical implications in education, supporting girls' anxiety, as this could have a negative impact on their academic performance and wellbeing.